Dependence of the Product's Phase Composition on the Ratio of Precursors in Plasmadynamic Synthesis of Silicon Carbide; Key Engineering Materials; Vol. 769 : High Technology: Research and Applications (HTRA 2017) - Sivkov A. A. Aleksandr Anatolyevich (2018, 2018)
Title screen